Changes in medical use of central nervous system stimulants among US adults, 2013 and 2018: a cross-sectional study - G Caleb Alexander; Thomas J Moore; Stefan P Kruszewski; Phillip W Wirtz (BMJ Open)
Objective To assess the 5-year changes in the adult medical use of central nervous system (CNS) stimulants with higher risk of dependence and evaluate the population characteristics of users and their medical and/or neurological conditions.Design Cross-sectional study.Setting Annual US Medical Expenditure Panel Survey, a stratified random sample of approximately 30 000 persons designed to produce national population estimates. It focuses on reported medical spending, medical services used, health status and prescription medications.Participants Adults age 19 years and older who reported obtaining one or more prescriptions for amphetamine or methylphenidate products during two survey years, 2013 and 2018.Main outcomes measures Prescriptions obtained, the specific stimulant product and annual treatment days of drug supplied.Results In 2018, an estimated 4.1 million US adults (95% CI 3.4 million to 4.8 million) reported prescriptions for CNS stimulants, having filled a mean of 7.3 (95% CI 6.8 to 7.8) prescriptions with a mean of 226 (95% CI 210 to 242) days’ supply. Compared with 2013, the estimated number of adults reporting using CNS stimulants in 2018 increased by 1.8 million (95% CI 1.0 million to 2.7 million) or 79.8%. Most 2018 adult stimulant users reported taking psychoactive medication for one or more mental, behavioural or neurodevelopment disorders. Overall, 77.8% (95% CI 72.6% to 83.0%) reported some medication for adult attention deficit disorder, 26.8% (95% CI 22.2% to 31.5%) took medication for anxiety, 25.1% (95% CI 19.9% to 30.3%) for depression and 15.3% (95% CI 9.8% to 20.8%) indicated drug treatment for other mental or neurological disorders. Adult CNS stimulant use was higher in females, in younger age cohorts and among individuals of white race/ethnicity.Conclusions Adult medical use of prescription stimulants increased markedly in 5 years and occurred in a population often reporting multiple mental or neurological disorders. Further action is needed to understand and manage this new resurgence in drugs with high risks of dependence.